2011
DOI: 10.3390/ijms12052891
|View full text |Cite
|
Sign up to set email alerts
|

The Different Muscle-Energetics during Shortening and Stretch

Abstract: The helical shape of the thin filaments causes their passive counterclockwise rotation during muscle stretch that increases tensile stress and torque at first by unwinding and then by winding up the four anchoring Z-filaments. This means storage of energy in the series elastic Z-filaments and a considerable decrease of the liberated energy of heat and work to (h—wap), where h is the heat energy and wap the stretch energy induced from outside by an apparatus. The steep thin filament helix with an inclination an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Four studies found that hamstring heating increased knee extension [12,17,43] [17] or untreated controls (MD, .36deg [95% CI, 4.87 to 5.59]). [43] These study results also agree with Chris M. and Joseph T, 2013 [9] It was concluded and there was clear evidence that combined heat and stretching is more effective than stretching alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies found that hamstring heating increased knee extension [12,17,43] [17] or untreated controls (MD, .36deg [95% CI, 4.87 to 5.59]). [43] These study results also agree with Chris M. and Joseph T, 2013 [9] It was concluded and there was clear evidence that combined heat and stretching is more effective than stretching alone.…”
Section: Discussionmentioning
confidence: 99%
“…Heat applied to peripheral tissues also can be used to increase the flexibility in body [12,13]. The application of heat reduces pain [14] and increase blood flow to tissue [15], Increasing soft tissue temperature prior to exercise is an accepted practice.…”
Section: Introductionmentioning
confidence: 99%
“…Actin is the main component of the thin filaments in muscle. During stretch and muscle contraction, the steep helical structure (70°) rotates and stores energy to aid the series elastic component in muscle [12]. This is due to the fact that the thin filaments are a double helix wound in a counter-clockwise rotation [43].…”
Section: Discussionmentioning
confidence: 99%
“…Heat also increases glycogen resynthesis and muscle recovery [10]. Heat is also cited as increasing flexibility and thus reducing the chance of injury, and reducing energy cost of muscle contraction by reducing internal friction [11,12]. Internal energy costs are reduced by warming muscle, but many of these studies have been done in animals and very few in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation